Если у вас нет собаки... - Ситников Юрий Вячеславович (Сибирская Благозвонница, 2016)
Экземпляры: ф.18 (20180529) / Инвентарный номер: 2970 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 41 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44